Investigation of the Incidence of Coital Incontinence in Incontinent Women - Omer Demir; Cihan Comba (Gynecology Obstetrics & Reproductive Medicine)
Objective: Coital incontinence is the involuntary leakage of urine during sexual intercourse and is rarely reported in women with urinary incontinence. The aim of this study is to investigate the frequency of coital incontinence and its association with incontinence types.